2021
DOI: 10.3390/fi13030080
|View full text |Cite
|
Sign up to set email alerts
|

A Web Interface for Analyzing Hate Speech

Abstract: Social media services make it possible for an increasing number of people to express their opinion publicly. In this context, large amounts of hateful comments are published daily. The PHARM project aims at monitoring and modeling hate speech against refugees and migrants in Greece, Italy, and Spain. In this direction, a web interface for the creation and the query of a multi-source database containing hate speech-related content is implemented and evaluated. The selected sources include Twitter, YouTube, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
0
19
0
5
Order By: Relevance
“…Online hate speech has been identified as a pressing problem in society, with experts from different fields of investigation looking for approaches to detect and prevent it. Recent research implements and evaluates innovative tools to deal with this phenomenon (Vrysis et al, 2021) and analyses emotional responses and the construction of "alternative counternarratives to this socially alive issue" (Ortega-Sánchez et al, 2021, p. 1).…”
Section: Cda Stage 5 Discussion: Reflections On the Analysis And The ...mentioning
confidence: 99%
“…Online hate speech has been identified as a pressing problem in society, with experts from different fields of investigation looking for approaches to detect and prevent it. Recent research implements and evaluates innovative tools to deal with this phenomenon (Vrysis et al, 2021) and analyses emotional responses and the construction of "alternative counternarratives to this socially alive issue" (Ortega-Sánchez et al, 2021, p. 1).…”
Section: Cda Stage 5 Discussion: Reflections On the Analysis And The ...mentioning
confidence: 99%
“…Other datasets were found that also contained texts in Spanish, but were not exclusively in Spanish, as in the case of the PHARM project, where the dataset is composed of texts in Spanish, Italian and Greek ( Vrysis et al, 2021 ).…”
Section: Related Workmentioning
confidence: 99%
“…Crowdsourcing is a methodology for distributed problem-solving that happens online by the collective intelligence of a community in a specific predefined direction set by an organization [49]. It has gained interest thanks to its efficiency and applicability in multiple domains and tasks [57][58][59][60][61]. In machine learning and automation, it has become very popular for collaborative problem solving and dataset formulation and validation [57,59].…”
Section: Crowdsourcing For Dataset Creation Validation and User Coope...mentioning
confidence: 99%
“…The web application was designed using the Flask web framework. This was a rational choice, taking into consideration the popularity of the Python programming language for data analysis and the successful deployment of similar web applications by our team [61]. The selection of a popular programming environment for such tasks may make the extendibility of the framework by contributors more appealing and viable.…”
Section: Implementation and Deployment Of The Prototype For Human-cen...mentioning
confidence: 99%